Structures, Occurrences and Biosynthesis of 11,12,13-Tri-nor-Sesquiterpenes, an Intriguing Class of Bioactive Metabolites - Víctor Coca-Ruíz; Ivonne Suárez; Josefina Aleu; Isidro G. Collado (Plants, 2022)
The compounds 11,12,13-tri-nor-sesquiterpenes are degraded sesquiterpenoids which have lost the C3 unit of isopropyl or isopropenyl at C-7 of the sesquiterpene skeleton. The irregular C-backbone originates from the oxidative removal of a C3 side chain from the C15 sesquiterpene, which arises from farnesyl diphosphate (FDP). The C12-framework is generated, generally, in all families of sesquiterpenes by oxidative cleavage of the C3 substituent, with the simultaneous introduction of a double bond. This article reviews the isolation, biosynthesis and biological activity of this special class of sesquiterpenes, the 11,12,13-tri-nor-sesquiterpenes.